Bringing Patient-Centered Care to the Fore in Diseases of the Pancreas - Sayali A. Pendharkar; Maxim S. Petrov (Gastroenterology Research and Practice)
Diseases of the pancreas are often very challenging for both patients and doctors as well as pose a considerable burden on healthcare system. Emerging evidence on the importance of shared-decision making in medicine stresses the need to integrate best clinical evidence and patient-reported outcomes to deliver optimal patient care. This paper argues that patient-centered care should no longer be a hermit in management of pancreatic diseases in the 21st century.